Economics, Political Practices and Identities on the Nile: Convergence and Conflicts ca. 1800 to 1530 BC - Flammini, Roxana Claudia (2020)
Political and economic networks which linked societies from the Levant to Nubia during the 2nd millennium BC were integrated as a world-system, fluctuating from a coreperiphery differentiation (ca. 2000 to 1800 BC) to a core-periphery hierarchy (ca. 1530 to 1200 BC) through a disruptive process which took place ca. 1800 to 1530 BC. This paper approaches this disruptive process, probably triggered by a legitimacy crisis in the core area. Disruption resulted in the emergence of a multiple independent cores; and also revealed local cultural features and practices. Despite the difficulties posed by the evidence, an attempt to analyse the relationships these political entities sustained is made.